Evaluation of antibacterial and cytotoxic effects of nano-sized bioactive glass/collagen composites releasing tetracycline hydrochloride - Rivadeneira, J.; Di Virgilio, A. L.; Audisio, M. C.; Boccaccini, Aldo R.; Gorustovich, A. A. (Journal of Applied Microbiology, 2014)
Aims: To evaluate the antibacterial efficacy of silicate bioactive glass nanoparticles/collagen composites functionalized with tetracycline hydrochloride (TCH). Methods and Results: Different concentrations of tetracycline hydrochloride (TCH) were incorporated on silicate bioactive glass nanoparticles/collagen composites by dipping these biomaterials for 48 h at 37°C in a solution of simulated body fluid (SBF) plus 0·05, 0·20 or 0·35 mg ml of the antibiotic. TCH release was assessed in double-distilled water at 37°C up to 72 h. The antibacterial activity of the samples has been evaluated in two ways: inhibition zone test and plate count method. The experiments were performed in vitro up to 48 h on four staphylococci strains (Staphylococcus aureus ATCC29213, ATCC25923, ATCC6538P and Staphylococcus epidermidis ATCC12228). The new composites were also tested for cytotoxicity on MG-63 human osteosarcoma cells. The results showed that the incorporation and release of TCH was dependent on the initial concentration of TCH in SBF. The biomaterials also inhibited the Staph. aureus cell growth even though the efficacy was similar for all concentration. On the other hand, no cytotoxic effects were found on osteoblast-like cells, even at the highest concentration. Conclusions: Considering all results, it can be concluded that the new composite acts as a suitable bioactive carrier of TCH and could have potential in the prevention of biomaterial related infections. Significance and Impact of the Study: The results suggest a potential application as wound dressing. © 2014 The Society for Applied Microbiology.
Keywords: Antibacterial activity; Antibiotic; Bioactive glass; Collagen